2020
DOI: 10.3389/fmed.2019.00336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 18F-FDG PET/CT in Staging Patients With Small Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Molecular imaging methods are currently used in the management of patients with lung cancer. Compared to non-small cell lung cancer, less data are available about the impact of molecular imaging using fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18 F-FDG PET/CT) in staging patients with small cell lung cancer (SCLC). Performing a systematic review and meta-analysis, we aimed to provide quantitative data about the impact of 18 F-FDG PET/CT in staging SCLC. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
1
29
0
1
Order By: Relevance
“…Volumetric parameters (MTV and TLG) have been confirmed as relevant for identifying patients with a higher risk of postsurgical disease progression who could receive early therapeutic intervention to improve their prognosis [ 83 ]. Similar meta-analysis was reported and indicated prognostic value of quantitative FDG uptake parameters in non-small cell lung cancer [ 84 ] and uterine cervical cancer [ 85 ].…”
Section: Clinical Applications Of Fdg Petsupporting
confidence: 77%
“…Volumetric parameters (MTV and TLG) have been confirmed as relevant for identifying patients with a higher risk of postsurgical disease progression who could receive early therapeutic intervention to improve their prognosis [ 83 ]. Similar meta-analysis was reported and indicated prognostic value of quantitative FDG uptake parameters in non-small cell lung cancer [ 84 ] and uterine cervical cancer [ 85 ].…”
Section: Clinical Applications Of Fdg Petsupporting
confidence: 77%
“…The use of FDGePET is still debated in SCLC; a review of small prospective series showed that 9% of patients were upstaged with FDGePET and 4% were downstaged. 13 In the majority of these series, pathological confirmation of metastatic sites was not obtained. As false-positive results have been reported using FDGePET, the presence of a metastasis should be pathologically confirmed if it alters the treatment plan [II, C].…”
Section: Staging and Risk Assessmentmentioning
confidence: 99%
“…Fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) is useful for SCLC staging because the detection rate of primary and metastatic lesions is very high due to the strong FDG accumulation [ 94 ]. Identifying NEPC, specifically by PET/CT, is difficult although PET/CT is also useful in detecting metastases in NEPC [ 95 ].…”
Section: Neuroendocrine Prostate Cancer (Nepc)mentioning
confidence: 99%